2023
DOI: 10.21203/rs.3.rs-2994622/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of morphological and biochemical variations in pea under two widespread abiotic stresses

Abstract: Pea is the third most widely grown leguminous vegetable crop in the world. The crop is fairly easy to grow but is salt and drought sensitive limiting its yield. The current study was, therefore, designed to explore the morphological and biochemical responses of pea under salt stress and water-deficit stress. For this purpose, three pea varieties namely Climax, Green grass and Meteor were subjected to different levels (5.4 mM (Control), 50 mM, 75 mM and 100 mM of NaCl) of salt stress. The water-deficit stress w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
1
0
0
Order By: Relevance
“…In the present study, salt stress significantly increased the contents of flavonoid and anthocyanin in all three cultivars. Similar results have been reported in Brassica napus (Kim et al, 2017) and pea (Farooq et al, 2021), which found that the contents of total flavonoid and phenolic compounds showed a significant increase to improve resistance in response to salt stress. In this study, JHR1 and JHB1 showed the higher increase of anthocyanin and flavonoid than YZ9102 under salt stress.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, salt stress significantly increased the contents of flavonoid and anthocyanin in all three cultivars. Similar results have been reported in Brassica napus (Kim et al, 2017) and pea (Farooq et al, 2021), which found that the contents of total flavonoid and phenolic compounds showed a significant increase to improve resistance in response to salt stress. In this study, JHR1 and JHB1 showed the higher increase of anthocyanin and flavonoid than YZ9102 under salt stress.…”
Section: Discussionsupporting
confidence: 89%